DIFFERENT METHODS IN LANGUAGE TEACHING - Yokubjonova, Dilnavozxon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This paper explores different new methods in language teaching. In this research, different types of teaching methods are widely used, such as Communicative Language Teaching (CLT), Language Teaching (LT), Presentation, Practice, Production ( PPP) and Grammar-Translation Method (GTM). In addition inductive learning approach is utilized rather than deductive learning approach in order to engage students and expand their knowledge. According to the research, it is obvious that learners’ needs is important in planning lesson to teach them effectively. Choosing authentic materials and instructions have been beneficial for students to improve their skills from listening, and speaking, reading and writing. From teaching methods Ppp method have been chosen according to its applicability, considering the time and students needs.